Using EPPM to Evaluate the Effectiveness of Fear Appeal Messages Across Different Media Outlets to Increase the Intention of Breast Self-Examination Among Chinese Women. - Chen, Liang; Yang, Xiaodong (Health Communication, 2019)
The current study aims to examine the influence of fear appeal messages across different media outlets on Chinese women's intention of breast self-examination using the Extended Parallel Processing Model (EPPM). A two-by-two-by-two factorial experiment is designed to examine the effect of threat and efficacy level of stimulus on different media outlets on behavioral intention. The sample includes 488 Chinese women who are between 25 and 50 years old. The results revealed that there were significant main effects of both threat and efficacy on the intention to performing breast self-examination. Moreover, the significant two-way interaction effect between threat and efficacy was detected, which indicated that Chinese women who received messages containing both high threat and high efficacy had the highest intention of breast self-examination. Besides, the results demonstrated that there was no significant difference in the effectiveness of fear appeal messages on between traditional and social media.